Investigation on corrosion behavior and mechanism of carbon steel under CaCO3 deposit in CO2-flooding environment. (December 2022) - He, San; Zhao, Haotong; Tontiwachwuthikul, Patioon; Qiu, Yunpeng; Luo, Siqi; Xia, Xingyu
Highlights: The CaCO3 deposit has a specific protective effect on the metal matrix. The corrosion behavior under CaCO3 deposit exists three periods. The self-catalytic effect of corrosion in the active area and the lattice dislocation effect of the compound salt are the main cause of pitting corrosion under CaCO3 deposit. Abstract: Under-deposit corrosion (UDC) is common in the wellbore and oil gathering and transmission systems, leading to system failure in severe cases. This study investigated the corrosion behavior and mechanism of carbon steel (L245N) under different thickness scales through weight loss experiment, potential dynamic polarization-scanning test, electrochemical impedance spectroscopy, scanning electron microscope, and energy-dispersive X-ray spectroscopy. The results show that a corrosion product film is formed on the surface of matrix covered with CaCO3 deposits. It has a specific protective effect on L245N steel, and however, the protective effect is limited. At 30°C, apparent pitting corrosion occurs on the metal matrix surface. The uniform corrosion rate of L245N steel decreases with an increase in the deposit layer thickness. The mechanism investigation results show that pitting corrosion under scale is caused by the autocatalytic effect in the activated zone and complex salt lattice dislocation. There are three reaction stages in the UDC process. Additionally, the anode process of under-deposit corrosion is controlled by activation and dissolution, and the cathodic process is mainly controlled by diffusion. However, the entire reaction process is controlled by the cathode.